Impact damage reduction of woven composites subject to pulse current - Li, Yan; Wang, Fusheng; Huang, Chenguang; Ren, Jianting; Wang, Donghong; Kong, Jie; Liu, Tao; Long, Laohu (Nature communications, 2023)
3D orthogonal woven composites are receiving increasing attention with the ever-growing market of composites. A current challenge for these materials’ development is how to improve their damage tolerance in orthogonal and layer-to-layer structures under extreme loads. In this paper, a damage reduction strategy is proposed by combining structural and electromagnetic properties. An integrated experimental platform is designed combining a power system, a drop-testing machine, and data acquisition devices to investigate the effects of pulse current and impact force on woven composites. Experimental results demonstrate that pulse current can effectively reduce delamination damage and residual deformation. A multi-field coupled damage model is developed to analyze the evolutions of temperature, current and damage. Parallel current-carrying carbon fibers that cause yarns to be transversely compressed enhance the mechanical properties. Moreover, the microcrack formation and extrusion deformation in yarns cause the redistribution of local current among carbon fibers, and its interaction with the self-field produces an obvious anti-impact effect. The obtained results reveal the mechanism of damage reduction and provide a potential approach for improving damage tolerance of these composites. In this work, the authors demonstrate that pulse current can effectively be used to reduce delamination damage and residual deformation in 3D orthogonal woven composites, enhancing mechanical properties and damage tolerance.